The novel 'Candidatus Amphibiichlamydia ranarum' is highly prevalent in invasive exotic bullfrogs (Lithobates catesbeianus). Issue 1 (6th June 2012) - Martel, An; Adriaensen, Connie; Sharifian‐Fard, Mojdeh; Vandewoestyne, Mado; Deforce, Dieter; Favoreel, Herman; Bergen, Karolien; Spitzen‐van der Sluijs, Annemarieke; Devisscher, Sander; Adriaens, Tim; Louette, Gerald; Baert, Kristof; et al.
Summary Knowledge concerning microbial infectious diseases in the current amphibian crisis is rudimentary and largely limited to ranavirosis and chytridiomycosis. The family Chlamydiaceae is gaining attention as a common cause of disease in amphibians and may harbour new and emerging amphibian pathogens. We identified a novel species of Chlamydiales (Candidatus Amphibiichlamydia ranarum) with a prevalence of 71% in exotic invasive bullfrog tadpoles (Lithobates catesbeianus) from an introduced population in the Netherlands. The sequence of a 1474 bp 16S rRNA gene fragment showed that the novel taxon forms a well‐defined clade with 'Candidatus Amphibiichlamydia salamandrae' within the Chlamydiaceae family. Although none of the tadpoles examined showed signs of clinical disease, urgent evaluation of its pathogenic potential for native amphibian species is required.